Developing cooperative learning in a content and language integrated learning context to enhance elementary school students' digital storytelling performance, English speaking proficiency, and financial knowledge - Fan, Ting‐Yu; Chen, Hsiu‐Ling (Journal of computer assisted learning, 2023)
Background Study English education has been promoted in Taiwan for many years. Recently, content and language integrated learning (CLIL) has received attention as an effective way to integrate English into real‐life contexts. With advances in technology, digital storytelling is suitable for students to develop multiple skills such as narrating real‐life stories and recording them in English. Objectives The present study developed a cooperative learning model in a CLIL context to enhance elementary school students' digital storytelling, English speaking proficiency performance, and financial knowledge. Methods The participants were 43 sixth‐grade students from two classes: the experimental group (n = 26) and the control group (n = 17). To investigate whether the digital storytelling results produced by the experimental group under the cooperative learning approach differed from the digital storytelling results produced individually by the control group, an experimental design was implemented throughout the 9‐week course. All the participants took financial knowledge and English‐speaking proficiency pre‐tests and then received financial knowledge classes and digital storytelling instruction to help them effectively design digital storytelling videos, which incorporated the concepts of financial knowledge and English‐speaking skills. Results and Conclusions The results showed that the experimental group outperformed the control group in the overall digital storytelling performance, English speaking proficiency, and financial knowledge. Lay Description What is already known about this topic CLIL is a teaching method in which language is a tool for learning both the content of a subject and the language itself. Digital storytelling enables users to develop multiple skills, such as organization and interpersonal skills. Cooperative Learning assists the integration of technology. What this paper adds An instructional design that uses digital storytelling to teach finance and English with CLIL. An experimental study among EFL elementary school students for acquiring financial knowledge and English speaking skills. Implications for practice and/or policy The course in this study may help EFL teachers by providing them with a basic financial knowledge curriculum in English for elementary school students. Cooperative learning through digital storytelling design for elementary school students may accelerate their organization and communication skills.